2010
DOI: 10.1002/cncr.25293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of tumor‐infiltrating lymphocytes for survival in stage II colon cancer

Abstract: BACKGROUND:The most reliable prognostic factor in colon cancer is the TNM classification. The objective of this study was to assess and compare the prognostic role of tumor-infiltrating lymphocytes (TILs) in stage II colon cancer. METHODS: Immunohistochemistry was used to assess the density of TILs that were positive for cluster of differentiation 3 (CD3) (T-cell coreceptor), CD45 isoform RO (CD45RO) (protein tyrosine phosphatase), nuclear transcription factor forkhead box P3 (FOXP3), and CD25 (a type I transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
98
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 72 publications
11
98
1
2
Order By: Relevance
“…A prognostic marker indicating risk of recurrence and cancer-related death is of particular clinical interest in stage II colorectal cancer, since high-risk patients within this subgroup may potentially benefit from adjuvant chemotherapy, which today is not routinely administered. Together with other stage-stratified results, 21,24,40,41,47,55,58 Figure 2 Cancer-specific survival in colorectal cancer patients with low (3-4), intermediate (5)(6), and high (7-12) total CD3 score (log rank Po0.0001). our findings justify the use of tumor infiltrating T cells as a prognostic marker in stage II colorectal cancer.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…A prognostic marker indicating risk of recurrence and cancer-related death is of particular clinical interest in stage II colorectal cancer, since high-risk patients within this subgroup may potentially benefit from adjuvant chemotherapy, which today is not routinely administered. Together with other stage-stratified results, 21,24,40,41,47,55,58 Figure 2 Cancer-specific survival in colorectal cancer patients with low (3-4), intermediate (5)(6), and high (7-12) total CD3 score (log rank Po0.0001). our findings justify the use of tumor infiltrating T cells as a prognostic marker in stage II colorectal cancer.…”
Section: Discussionsupporting
confidence: 52%
“…58 T-cell infiltration is not homogeneous in colorectal cancer, and attention has therefore also been focused on the predictive values of T cells in different tumor compartments. 32,33,37,[42][43][44][45][46][47] In this study, the separate measurements of T-cell infiltration in the tumor front, center, and intraepithelial compartment were closely correlated and were all positively associated with cancer-specific survival. Two previous studies found that a high total lymphocyte score, similar to that used in this study, more accurately predicted cancer-specific survival compared with any single score separately.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Immunohistochemical studies in CRC have been directed to the detection of the origin of metastatic colonic lesions and CRC prognosis with discordant results (44,45). We did not find any publication focused on the possible value of immunohistochemistry for the assessment of tumor multicentricity risk, which is the principal topic of our research.…”
Section: Discussionmentioning
confidence: 90%
“…Hierarchical cluster analysis of the 11 CRC and TIL antigens produced similar groups of patients that were separated into three categories (relapse-free, systemic relapse, and cancer-specific death), supporting the hypothesis that surface antigen profiles on CRC cells and TIL yield prognostic information. (Wagner et al, 2001;Shelley et al, 2002;Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%